Reflections on Capital Punishment - Warden, Rob (2009)
Authored by the Executive Director of the Center on Wrongful Convictions, this powerful article reviews the many different arguments against the death penalty and uses a multitude of case discussions to show how the death penalty works, not in theory, but in practice. Some of these arguments include: the death penalty does not have a demonstrable deterrent effect; it costs more to maintain the system than to imprison murderers for life; many wrongfully condemned defendants have been saved by the serendipitous discovery of evidence not available during trial; innocent persons have been executed; the death penalty has been applied in a freakish manner and not pain-free; and time and geography often is the deciding factor in capital and non-capital cases. The Article uses the case discussions to conclude that the death penalty is more objectionable today than ever before